Adhesive for aging-resistant, high-strength and high-toughness copper-clad plate, preparation method of adhesive and PI adhesive tape
By using rigid epoxy resin and isocyanate toughener in flexible copper clad adhesives to form an interpenetrating network structure, combining flexible epoxy resin and flame retardant, the performance degradation of existing adhesives after thermal aging and humidity-heat aging is solved. The problem is that high bonding force, toughness and soldering resistance have been improved, and the service life has been extended.
Patent Information
- Application Number
- CN202411502904.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
AI Technical Summary
After the existing adhesives for flexible copper clad plates are thermally aged and the resin has a sharp decline in peeling force and electrical insulation performance, and the service life is short. Polyester adhesives are prone to decomposition and produce bubbles during high-temperature welding, which affects performance. .
Using components including rigid epoxy resin and isocyanate toughener, an interpenetrating network structure is formed through a unique heating process, combining flexible epoxy resin and flame retardant, aging-resistant high strength and high toughness adhesive is prepared, and It is evenly coated onto a polyimide film and baked to form a PI tape.
It realizes high adhesion, strong toughness and good heat resistance of the adhesive, avoids the disadvantages of inadequate aging, enhances the soldering resistance, and maintains excellent peeling force and flame retardant properties after thermal aging and humidity and heat aging. .
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesive materials, and in particular to an adhesive for an aging-resistant high-strength and high-toughness copper-clad laminate, a preparation method thereof, and a PI tape. Background Art
[0002] Since the beginning of this century, with the continuous development of my country in the fields of digital 3C, aerospace, and medical, the level of localization of high-end industries has been continuously improved, and the output has increased significantly. This has also greatly increased the production capacity and sales of flexible copper clad laminates. In recent years, with the saturated supply of high-end application fields, the market and industry have continuously improved the performance requirements of flexible copper clad laminates. So far, most of the adhesives used in flexible copper clad laminates are rubber toughening agent toughened epoxy resins (CN116515239A). Although this type of adhesive has the advantages of high adhesion, high strength and high heat resistance, after heat aging and wet heat aging, the resin ages rapidly, and the peeling force and electrical insulation performance drop significantly. Therefore, this type of copper clad laminate adhesive has a narrow range of use, harsh storage and use conditions, and a short service life. The development of high-end flexible copper clad laminates that also have high adhesion, high strength, high heat resistance and aging resistance has very important social and commercial significance.
[0003] 1. The current mainstream rubber toughened epoxy resin adhesive for flexible copper clad laminates has poor resistance to moisture and heat aging and heat aging, and has a short service life.
[0004] 2. There are different types of polyester copper clad laminate adhesives on the market. Some polyester adhesives have poor resistance to moisture and heat, and polyester adhesives have poor resistance to soldering. During the production and application of copper clad laminates, most of them must undergo reflow soldering at temperatures above 260°C. Polyester adhesives are prone to decomposition under these conditions to produce bubbles and cause performance degradation. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an adhesive for copper-clad laminates with high strength and toughness and aging resistance, a preparation method thereof and a PI tape in view of the deficiencies in the above-mentioned prior art.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, an adhesive for copper clad laminate with high strength and high toughness and aging resistance is provided, comprising component A and component B, wherein component A comprises the following components in parts by weight:
[0007] 30-60 parts of rigid epoxy resin;
[0008] 2-8 parts of isocyanate toughening agent;
[0009] The B component includes the following components by weight:
[0010]
[0011] Preferably, the rigid epoxy resin is one or a mixture of two of novolac epoxy resin and dicyclopentadiene phenol epoxy resin.
[0012] Preferably, the isocyanate toughening agent is one or a mixture of two of HDI (hexamethylene diisocyanate) and HDI trimer (hexamethylene diisocyanate trimer).
[0013] Preferably, the flexible amine curing agent is one or a mixture of aromatic amine and alicyclic amine.
[0014] Preferably, the flexible epoxy resin is a mixture of one or both of polyether-modified epoxy resin and dimer acid-modified epoxy resin.
[0015] Preferably, the flame retardant is one or a mixture of OP935 (diethylaluminum hypophosphite) and ammonium polyphosphate.
[0016] Preferably, the antioxidant is one or a mixture of tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl)bisphosphite, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, 4,4'-di(phenylisopropyl)diphenylamine and tris(2,4-di-tert-butylphenyl)phosphite.
[0017] A second aspect of the present invention provides a method for preparing the above-mentioned aging-resistant high-strength and high-toughness copper-clad laminate adhesive, comprising the following steps:
[0018] S1, dissolving a rigid epoxy resin and an isocyanate toughening agent in a solvent to prepare a solution of component A with a concentration of 30 wt%, and treating at 40° C. for 24 h;
[0019] S2, dissolving a flexible amine curing agent, a flexible epoxy resin, a polyester toughening agent, a flame retardant, and an antioxidant in a solvent to prepare a solution of component B with a concentration of 30 wt%;
[0020] S3. Evenly mix the product of step S1 and the product of step S2 to obtain an adhesive for copper-clad laminates with high strength and toughness and aging resistance.
[0021] Preferably, the solvent is one or a mixture of butanone, ethyl acetate and n-butyl acetate.
[0022] The third aspect of the present invention provides a PI tape for an aging-resistant, high-strength and high-toughness copper-clad laminate, characterized in that it is prepared by the following method: the above-mentioned aging-resistant, high-strength and high-toughness adhesive for copper-clad laminates is evenly coated on a polyimide film, baked at 130°C for 5 minutes, and affixed to the adhesive surface with a release film to obtain the aging-resistant, high-strength and high-toughness adhesive for copper-clad laminates.
[0023] The beneficial effects of the present invention are:
[0024] The invention provides an adhesive for copper-clad laminates with high strength and high toughness and aging resistance, a preparation method thereof and a PI tape. The PI tape prepared by the invention has high bonding force, strong toughness, good heat resistance and excellent comprehensive performance. Currently, most conventional adhesives for flexible copper-clad laminates use rubber-toughened epoxy resins, which have the disadvantage of being not resistant to aging. However, the invention does not use rubber materials containing double bonds, thereby avoiding the disadvantage of being not resistant to aging.
[0025] The toughening agent and flexible epoxy selected in the adhesive formula of the present invention are both toughening materials with special aging resistance advantages, most of which are high temperature resistant structures and have excellent solder resistance.
[0026] The component A of the present invention forms an interpenetrating network structure by adopting a unique heating process, which can improve toughness and adhesion without reducing solder resistance, so that the adhesive has good toughness even without a high-toughness rubber toughening agent. The formation mechanism of the interpenetrating network structure is as follows: the epoxy group and the isocyanate group react at a low reaction rate in a 40°C oven to form a rigid cross-linked structure, while the isocyanates are trimerized to form a flexible cross-linked structure. Since the formation of the cross-linked network is relatively slow, the chain segments formed by the trimerization of the isocyanates grow and entangle along the rigid network phase; the two slowly form a entangled network structure, so that the component A is a solution containing a part of the interpenetrating network; since the solvent exists inside the cross-linked network, when the component B is subsequently introduced, the part of the interpenetrating network in the component A exists in the overall cross-linked network, which plays a role in toughening and strengthening. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0028] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0029] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0030] The present invention provides an adhesive for an aging-resistant, high-strength, high-toughness copper-clad laminate, comprising a component A and a component B, wherein the component A comprises the following components in parts by weight:
[0031] 30-60 parts of rigid epoxy resin;
[0032] 2-8 parts of isocyanate toughening agent;
[0033] Component B includes the following components by weight:
[0034]
[0035] In a preferred embodiment, the rigid epoxy resin is one of novolac epoxy resin and dicyclopentadiene phenol epoxy resin or a mixture of both.
[0036] In a preferred embodiment, the isocyanate toughening agent is one or a mixture of two of HDI (hexamethylene diisocyanate) and HDI trimer (hexamethylene diisocyanate trimer).
[0037] In a preferred embodiment, the flexible amine curing agent is an aromatic amine, an alicyclic amine, or a mixture of both.
[0038] In a preferred embodiment, the flexible epoxy resin is a mixture of one or both of a polyether-modified epoxy resin and a dimer acid-modified epoxy resin.
[0039] In a preferred embodiment, the flame retardant is one or a mixture of OP935 (diethylaluminum hypophosphite) and ammonium polyphosphate.
[0040] In a preferred embodiment, the antioxidant is one or a mixture of tetrakis(2,4-di-tert-butylphenyl-4,4'-biphenyl)bisphosphite, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, 4,4'-di(phenylisopropyl)diphenylamine and tris(2,4-di-tert-butylphenyl)phosphite.
[0041] The present invention also provides a method for preparing the above-mentioned aging-resistant high-strength and high-toughness adhesive for copper-clad laminates, comprising the following steps:
[0042] S1, dissolving a rigid epoxy resin and an isocyanate toughening agent in a solvent to prepare a solution of component A with a concentration of 30 wt%, and treating at 40° C. for 24 h;
[0043] S2, dissolving a flexible amine curing agent, a flexible epoxy resin, a polyester toughening agent, a flame retardant, and an antioxidant in a solvent to prepare a solution of component B with a concentration of 30 wt%;
[0044] S3. Evenly mix the product of step S1 and the product of step S2 to obtain an adhesive for copper-clad laminates with high strength and toughness and aging resistance.
[0045] In a preferred embodiment, the solvent is one or a mixture of butanone, ethyl acetate and n-butyl acetate.
[0046] The present invention also provides an aging-resistant high-strength and high-toughness PI tape for copper-clad laminates, which is prepared by the following method: uniformly coating the above-mentioned aging-resistant high-strength and high-toughness adhesive for copper-clad laminates on a polyimide film, baking at 130° C. for 5 minutes, and laminating a release film on the adhesive surface to obtain the aging-resistant high-strength and high-toughness adhesive for copper-clad laminates.
[0047] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0048] Example 1
[0049] A PI tape for an aging-resistant, high-strength, high-toughness copper-clad laminate, the preparation method of which comprises the following steps:
[0050] 30 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 20 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 3 parts of HDI (Wanhua Chemical), and 3 parts of HDI trimer (Covestro, Germany) were dissolved in n-butyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0051] 16 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 18 parts of R-2217 aromatic amine curing agent (Rich Chemical), 5 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 5 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 10 parts of HIPES 90A polyester (SK Chemical, South Korea), 18 parts of OP935 (Clariant, Switzerland), and 3 parts of tetrakis (2, 4-di-tert-butylphenyl-4, 4'-biphenyl) bisphosphonite (Tianjin Lianlong) were dissolved in n-butyl acetate solution to prepare a 30wt% solution of component B.
[0052] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0053] Example 2
[0054] A PI tape for an aging-resistant, high-strength, high-toughness copper-clad laminate, the preparation method of which comprises the following steps:
[0055] 20 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 30 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 5 parts of HDI (Wanhua Chemical), and 2 parts of HDI trimer (Covestro, Germany) were dissolved in ethyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0056] 16 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 18 parts of R-2217 aromatic amine curing agent (Rich Chemical), 5 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 5 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 10 parts of HIPES 90A polyester (SK Chemical, South Korea), 18 parts of OP935 (Clariant, Switzerland), and 3 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (Tianjin Lianlong) were dissolved in n-ethyl acetate solution to prepare a 30wt% solution of component B.
[0057] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0058] Example 3
[0059] 30 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 20 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 3 parts of HDI (Wanhua Chemical), and 3 parts of HDI trimer (Covestro, Germany) were dissolved in n-butyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0060] 25 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 10 parts of R-2217 aromatic amine curing agent (Rich Chemical), 7 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 6 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 20 parts of HIPES 90A polyester (SK Chemical, South Korea), 12 parts of OP935 (Clariant, Switzerland), 3 parts of bis(3,5-di-tert-butyl-4-hydroxy-phenylpropionyl)hydrazine, and 4,4'-di(phenylisopropyl)diphenylamine (Tianjin Lianlong) were dissolved in n-butyl acetate solution to prepare a 30wt% solution of component B.
[0061] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0062] Comparative Example 1
[0063] 50 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 20 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 3 parts of HDI (Wanhua Chemical), and 3 parts of HDI trimer (Covestro, Germany) were dissolved in n-butyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0064] 16 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 18 parts of R-2217 aromatic amine curing agent (Rich Chemical), 5 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 5 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 10 parts of HIPES 90A polyester (SK Chemical, South Korea), 18 parts of OP935 (Clariant, Switzerland), and 3 parts of tetrakis (2, 4-di-tert-butylphenyl-4, 4'-biphenyl) bisphosphonite (Tianjin Lianlong) were dissolved in n-butyl acetate solution to prepare a 30wt% solution of component B.
[0065] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0066] Comparative Example 2
[0067] 30 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 20 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 10 parts of HDI (Wanhua Chemical), and 3 parts of HDI trimer (Covestro, Germany) were dissolved in n-butyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0068] 16 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 18 parts of R-2217 aromatic amine curing agent (Rich Chemical), 5 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 5 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 10 parts of HIPES 90A polyester (SK Chemical, South Korea), 18 parts of OP935 (Clariant, Switzerland), and 3 parts of tetrakis (2, 4-di-tert-butylphenyl-4, 4'-biphenyl) bisphosphonite (Tianjin Lianlong) were dissolved in n-butyl acetate solution to prepare a 30wt% solution of component B.
[0069] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0070] Comparative Example 3
[0071] 30 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 20 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 3 parts of HDI (Wanhua Chemical), and 3 parts of HDI trimer (Covestro, Germany) were dissolved in n-butyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0072] 30 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 30 parts of R-2217 aromatic amine curing agent (Rich Chemical), 5 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 5 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 10 parts of HIPES 90A polyester (SK Chemical, South Korea), 18 parts of OP935 (Clariant, Switzerland), and 3 parts of tetrakis (2, 4-di-tert-butylphenyl-4, 4'-biphenyl) bisphosphonite (Tianjin Lianlong) were dissolved in n-butyl acetate solution to prepare a 30wt% solution of component B.
[0073] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0074] Comparative Example 4
[0075] 30 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 20 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 3 parts of HDI (Wanhua Chemical), and 3 parts of HDI trimer (Covestro, Germany) were dissolved in n-butyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0076] 16 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 18 parts of R-2217 aromatic amine curing agent (Rich Chemical), 5 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 5 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 10 parts of HIPES 90A polyester (SK Chemical, South Korea), 8 parts of OP935 (Clariant, Switzerland), and 3 parts of tetrakis (2, 4-di-tert-butylphenyl-4, 4'-biphenyl) bisphosphonite (Tianjin Lianlong) were dissolved in n-butyl acetate solution to prepare a 30wt% solution of component B.
[0077] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0078] Comparative Example 5
[0079] 30 parts of NPPN-631 phenolic epoxy resin (Nan Ya, Taiwan, China), 20 parts of DNE260 dicyclopentadiene phenol epoxy resin (Changchun, Taiwan, China), 3 parts of HDI (Wanhua Chemical), and 3 parts of HDI trimer (Covestro, Germany) were dissolved in n-butyl acetate to prepare a 30 wt% solution of component A, which was placed in an oven at 40°C and reacted for 24 hours.
[0080] 16 parts of R-2028 alicyclic amine curing agent (Rich Chemical), 18 parts of R-2217 aromatic amine curing agent (Rich Chemical), 5 parts of EP-4000 polyether modified epoxy resin (Japan Aidico), 5 parts of NPER-172 dimer acid modified epoxy resin (Nanya, Taiwan, China), 10 parts of HIPES 90A polyester (SK Chemical, South Korea), and 18 parts of OP935 (Clariant, Switzerland) were dissolved in n-butyl acetate solution to prepare a 30wt% solution of component B.
[0081] After the prepared solution of component A and the solution of component B are evenly mixed, the adhesive solution is applied on the polyimide film, and the coating thickness of the dry adhesive after curing is controlled to be 30 μm. After it is baked at 130°C for 5 minutes, the surface is covered with release paper to obtain the PI tape for copper clad laminate with high strength and toughness and aging resistance.
[0082] The following performance tests were performed on the PI tapes prepared in the above Examples 1-3 and Comparative Examples 1-5.
[0083] 1. T-peel separation force test
[0084] (1) After sampling at different positions of the tape, place it in a standard environment for 24 hours;
[0085] (2) Cut the tape into 25.4mm*300mm pieces, 5 pieces in total;
[0086] (3) Peel off the release layer of the tape, and at 60° C., use a rubber roller to stick the two adhesive surfaces to each other or to the copper foil, and then form them by hot pressing at a temperature of 120-180° C. for 20-60 seconds to obtain a tape for PI flexible copper clad laminate and a tape for PI flexible copper clad laminate to copper.
[0087] (4) Place it at 160-180°C and cure for about 2 hours.
[0088] (5) After curing, the test is carried out in accordance with GB / T 2792-2014 standard, with the requirement of >2500gf / inch.
[0089] 2. 300℃ soldering test
[0090] (1) Prepare adhesive tape for bonding PI flexible copper clad laminate according to the test item described in 1.
[0091] (2) Test the adhesive tape for bonding PI flexible copper clad laminates according to IPC-TM-650 2.4.13, test conditions 300℃×10s;
[0092] (3) If there is no obvious change in appearance, no delamination, bubbles, etc., it means that the appearance is OK.
[0093] 3. Thermal aging test
[0094] (1) According to the test process of test item 1, prepare adhesive tape for bonding and copper PI flexible copper clad laminate;
[0095] (2) Place the adhesive tape for the bonding and copper PI flexible copper clad laminate in a 130°C oven and bake for about 500 hours. Take it out and measure it according to GB / T 2792-2014 standard, with the requirement of >2000gf / inch.
[0096] 4. Wet heat aging test;
[0097] (1) According to the test process of test item 1, prepare adhesive tape for bonding and copper PI flexible copper clad laminate;
[0098] (2) Place the adhesive tape for the bonding and copper PI flexible copper clad laminate in an 85°C × / 85% RH environment box and age for about 1000 hours. Take it out and measure it according to GB / T 2792-2014 standard, with the requirement of >2000gf / inch.
[0099] 5. UL 94VTM-0, VTM-1, VTM-2 vertical combustion test
[0100] Test method: Perform flame retardant test on uncured PI tape according to UL-94 test standard. Flame retardant grade VTM-0 is required.
[0101] The test results are shown in Table 1 below:
[0102] Table 1
[0103]
[0104]
[0105] According to the test results in Table 1, it can be seen that the PI tapes prepared in Examples 1-3 have high adhesion, strong toughness, good heat resistance, and excellent comprehensive performance;
[0106] Compared with Examples 1-3, the excessive addition of NPPN-631 in Comparative Example 1 resulted in a lower degree of crosslinking of the adhesive layer and a peel force lower than 2500 gf / inch.
[0107] Compared with Examples 1-3, the excessive amount of HDI added in Comparative Example 2 resulted in a large cross-linked network formed in Component A, which formed insoluble matter and could not be completely dispersed in the glue, ultimately resulting in particles on the surface of the coating. These particles did not participate in the cross-linked network and caused a decrease in peeling force after aging. At the same time, the particles contained more non-reactive groups, and the solder was easily decomposed to cause bubbles.
[0108] Compared with Examples 1-3, the excessive addition of R-2028 and R-2217 in Comparative Example 3 resulted in an excessively high crosslinking density of the adhesive layer, making the adhesive layer brittle, and a peeling force lower than 2500 gf / inch.
[0109] Compared with Examples 1-3, the amount of OP935 added in Comparative Example 4 is too small, resulting in insufficient flame retardancy of the adhesive layer, and the flame retardancy level of VTM-0 cannot be achieved.
[0110] Compared with Examples 1-3, in Comparative Example 5, tetrakis(2,4-di-tert-butylphenyl-4,4'biphenyl)bisphosphonite was not added, which affected the anti-aging performance of the cross-linked network. After heat aging and wet heat aging, the peel force dropped significantly to less than 1000 gf / inch.
[0111] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. An adhesive for an aging-resistant, high-strength, high-toughness copper-clad laminate, characterized in that: It comprises component A and component B, wherein component A comprises the following components in parts by weight: 30-60 parts of rigid epoxy resin; 2-8 parts of isocyanate toughening agent; The B component includes the following components by weight:
2. The aging-resistant high-strength and high-toughness adhesive for copper-clad laminates according to claim 1, characterized in that: The rigid epoxy resin is one of phenolic epoxy resin and dicyclopentadiene phenol epoxy resin or a mixture of both.
3. The aging-resistant high-strength and high-toughness adhesive for copper-clad laminates according to claim 1, characterized in that: The isocyanate toughening agent is one or a mixture of hexamethylene diisocyanate and hexamethylene diisocyanate trimer.
4. The aging-resistant high-strength and high-toughness adhesive for copper-clad laminates according to claim 1, characterized in that: The flexible amine curing agent is one of aromatic amine and alicyclic amine or a mixture of both.
5. The aging-resistant high-strength and high-toughness adhesive for copper-clad laminates according to claim 1, characterized in that: The flexible epoxy resin is one or a mixture of polyether modified epoxy resin and dimer acid modified epoxy resin.
6. The aging-resistant high-strength and high-toughness adhesive for copper-clad laminates according to claim 1, characterized in that: The flame retardant is one of diethyl aluminum hypophosphite and ammonium polyphosphate or a mixture of both.
7. The aging-resistant high-strength and high-toughness adhesive for copper-clad laminates according to claim 1, characterized in that: The antioxidant is one of tetrakis (2, 4-di-tert-butylphenyl-4, 4'-biphenyl) bisphosphite, tetrakis [β-(3, 5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, bis (3, 5-di-tert-butyl-4-hydroxy-phenylpropionyl) hydrazine, 4, 4'-di (phenyl isopropyl) diphenylamine and tris (2, 4-di-tert-butylphenyl) phosphite or a mixture of several thereof.
8. A method for preparing an adhesive for an aging-resistant, high-strength, high-toughness copper-clad laminate according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, dissolving a rigid epoxy resin and an isocyanate toughening agent in a solvent to prepare a solution of component A with a concentration of 30 wt%, and treating at 40° C. for 24 h; S2, dissolving a flexible amine curing agent, a flexible epoxy resin, a polyester toughening agent, a flame retardant, and an antioxidant in a solvent to prepare a solution of component B with a concentration of 30 wt%; S3. Evenly mix the product of step S1 and the product of step S2 to obtain an adhesive for copper-clad laminates with high strength and toughness and aging resistance.
9. The method for preparing the aging-resistant high-strength and high-toughness adhesive for copper-clad laminates according to claim 8, characterized in that: The solvent is one or a mixture of butanone, ethyl acetate and n-butyl acetate.
10. A PI tape for aging-resistant, high-strength and high-toughness copper-clad laminate, characterized in that: The adhesive is prepared by the following method: the adhesive for the aging-resistant, high-strength and high-toughness copper-clad laminate described in any one of claims 1 to 7 is evenly coated on a polyimide film, baked at 130° C. for 5 minutes, and affixed to the adhesive surface with a release film to obtain the adhesive for the aging-resistant, high-strength and high-toughness copper-clad laminate.
Citation Information
Patent Citations
Resin composition and cover film
CN116515239A